2021
DOI: 10.3390/diagnostics11112017
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Method to Enhance Thick and Thin Vessels for Blood Vessel Segmentation

Abstract: Retinal blood vessels have been presented to contribute confirmation with regard to tortuosity, branching angles, or change in diameter as a result of ophthalmic disease. Although many enhancement filters are extensively utilized, the Jerman filter responds quite effectively at vessels, edges, and bifurcations and improves the visualization of structures. In contrast, curvelet transform is specifically designed to associate scale with orientation and can be used to recover from noisy data by curvelet shrinkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Additionally machine learning, deep learning, and stochastic Markov chain distribution [ 40 ] will envision mathematical modeling not only for CCs but also for different diseases. Further, image classification, data-driven classification models, disease detection, feature classification, and blood vessel segmentation for CCs can be utilized to give possible solutions in the near future [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally machine learning, deep learning, and stochastic Markov chain distribution [ 40 ] will envision mathematical modeling not only for CCs but also for different diseases. Further, image classification, data-driven classification models, disease detection, feature classification, and blood vessel segmentation for CCs can be utilized to give possible solutions in the near future [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…When segmenting data, Mean-C thresholding is used. Average accuracy for the suggested method is 0.9559 and 0.9600 [80].…”
Section: Introductionmentioning
confidence: 97%
“…Jiang et al suggested a bilateral network with scale attention for the segmentation of vessels [45]. Dash et al suggested a hybrid technique for the extraction of thin and thick vessels [46]. Kovacs and Fazekas recommended a new baseline for blood vessel segmentation [47].…”
Section: Introductionmentioning
confidence: 99%